2023
DOI: 10.3389/fimmu.2023.1098140
|View full text |Cite
|
Sign up to set email alerts
|

Identifying TNF and IL6 as potential hub genes and targeted drugs associated with scleritis: A bio-informative report

Abstract: BackgroundScleritis is a serious inflammatory eye disease that can lead to blindness. The etiology and pathogenesis of scleritis remain unclear, and increasing evidence indicates that some specific genes and proteins are involved. This study aimed to identify pivotal genes and drug targets for scleritis, thus providing new directions for the treatment of this disease.MethodsWe screened candidate genes and proteins associated with scleritis by text-mining the PubMed database using Python, and assessed their fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…IL-22 typically protects against bacterial and fungal infections, but recent findings suggest that it amplifies the effects of other cytokines that are known to be involved in ocular inflammation, such as interleukin 1-β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and IL-17. Additionally, elevated levels of IL-22 were detected in patients with scleritis and episcleritis [42,44].…”
Section: Episcleritismentioning
confidence: 98%
See 1 more Smart Citation
“…IL-22 typically protects against bacterial and fungal infections, but recent findings suggest that it amplifies the effects of other cytokines that are known to be involved in ocular inflammation, such as interleukin 1-β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and IL-17. Additionally, elevated levels of IL-22 were detected in patients with scleritis and episcleritis [42,44].…”
Section: Episcleritismentioning
confidence: 98%
“…The inflammation is mediated by the activation of resident immunity cells releasing cytokines and inducing vasodilation with vessels' engorgement [42]. De la Maza et al reported a potential role of interleukin-22 (IL-22) in the pathogenesis of episcleritis and scleritis [43,44]. IL-22 typically protects against bacterial and fungal infections, but recent findings suggest that it amplifies the effects of other cytokines that are known to be involved in ocular inflammation, such as interleukin 1-β (IL-1β), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and IL-17.…”
Section: Episcleritismentioning
confidence: 99%
“…Neben den konventionellen synthetischen (insbesondere MTX) werden die biologischen (z. B. Anti-IL-6, Anti-TNF) [14] oder Targeted Synthetic DMARDs (ts; Tofacitinib, Baricitinib) wegen des schnellen Wirkungseintritts und der guten Verträglichkeit zunehmend favorisiert [15]. Bei besonders schwerem Verlauf von RA und Skleritis (insbesondere mit Nekrose) können Rituximab (Anti-CD-20-Antikörper) [16] oder kombiniert Cyclophosphamid-Puls und Plasmapherese angezeigt sein.…”
Section: Augenbeteiligung Bei Rheumatoider Arthritis (Ra)unclassified
“…In the case of a recurrent or particularly severe disease course with the occurrence of secondary complications threatening visual acuity (e.g., ulcerative keratitis, exudative retinal detachment), an interdisciplinary decision must be made on the use or intensification of treatment with DMARDs. In addition to conventional synthetic DMARDs (in particular MTX), biological (e.g., anti-IL-6, anti-TNF) [14] or targeted synthetic (ts) (tofacitinib, baricitinib) DMARDs are increasingly favored because of their rapid effect and good tolerability [15]. In particularly severe courses of RA and scleritis (especially with necrosis), rituximab (anti-CD-20 antibody) [16] or combined pulse cyclophosphamide and plasmapheresis may be indicated.…”
Section: Ocular Involvement In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%